Phonological Features of Angry Register Expressions in Bikol-Naga: An Acoustic Analysis Across Age Groups - Ocampo, Darrel M. (Program Studi Pendidikan Bahasa Inggris, 2025)
This study investigated the phonological characteristics of angry register expressions in Bikol-Naga as uttered by high school students, college students, teachers, and laborers. Utilizing Praat software for acoustic analysis, variations in pitch and intensity contours of selected angry words were examined. Findings indicate that while universal vocal signals of anger, such as elevated pitch and increased intensity, are present across all groups, culturally specific vocal components and controlled delivery patterns are also evident, particularly among older speakers and those in more formal professions. The analysis reveals how prosodic elements like pitch and intensity, alongside specific phonological features such as glottal stops and voiced velar fricatives, contribute to the expression and interpretation of anger in Bikol-Naga, aligning with existing research on emotional speech and language-specific phonology. This research contributes to a deeper understanding of the socio-phonetic variations of emotional speech in Philippine languages.